2006
DOI: 10.1177/026010600601800210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Frozen Period on The Chemical, Microbiological and Sensory Quality of Frozen Tilapia Fish (Sarotherodun Galiaenus)

Abstract: The study was designed to investigate the effect of duration of frozen storage on the chemical, microbiological and sensory profile of Tilapia fish (Sarotherodun galiaenus) collected from a research pond of the Agricultural Development Project, Akure, Nigeria, subjected to sixty days of frozen storage and analyzed at intervals of ten days. Protein content (%) ranges from 43.70 +/- 1.17-60.65 +/- 2.40. Protein decreases with increasing duration of frozen storage with the fresh samples (not frozen) having the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
70
2
8

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(105 citation statements)
references
References 16 publications
25
70
2
8
Order By: Relevance
“…This finding is in agreement with the findings of Aranilewa et al [23] where an increasing coliform count with a prolonged frozen storage of fish was observed. They argued that possible temperature fluctuations of the freezers, time taken during the processing, time taken to transport and trade the fish might have contributed to the high coliform counts.…”
Section: Prevalence Of Total Coliforms (Tc) Fecal Coliforms (Fc) Andsupporting
confidence: 94%
“…This finding is in agreement with the findings of Aranilewa et al [23] where an increasing coliform count with a prolonged frozen storage of fish was observed. They argued that possible temperature fluctuations of the freezers, time taken during the processing, time taken to transport and trade the fish might have contributed to the high coliform counts.…”
Section: Prevalence Of Total Coliforms (Tc) Fecal Coliforms (Fc) Andsupporting
confidence: 94%
“…According to Poli et al (2005), pH of fresh fish is around 6.5. Storage time tends to increase the pH values which can be associated with the production of basic components such as ammonia, volatile alkali and trimetilamin due to internal enzymatic activity and the growth of bacteria (Simeonidou et al, 1998;Arannilewa et al, 2005;Chamarana et al, 2012). In this study, TVB value might not showing correlation with pH due to washing effect of ice (Figure 2), but the increase of total bacteria count during storage (Table 3) indicated that there was a correlation between pH and the growth of bacteria.…”
Section: Phmentioning
confidence: 99%
“…Dried fish is one of the most important sources of animal protein and other essential nutrients for the maintenance of a healthy body [1]. Moreover, Bangladeshi people from northeastern, central, and coastal areas highly prefer this dried fish due to its characteristic taste and flavor.…”
Section: Introductionmentioning
confidence: 99%